Biological synthesis of metallic nanoparticles and their interactions with various biomedical targets - Sennuga, Afolake Temitope (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2012)
The synthesis of nanostructured materials, especially metallic nanoparticles, has accrued utmost interest over the past decade owing to their unique properties that make them applicable in different fields of science and technology. The limitation to the use of these nanoparticles is the paucity of an effective method of synthesis that will produce homogeneous size and shape nanoparticles as well as particles with limited or no toxicity to the human health and the environment. The biological method of nanoparticle synthesis is a relatively simple, cheap and environmentally friendly method than the conventional chemical method of synthesis and thus gains an upper hand. The biomineralization of nanoparticles in protein cages is one of such biological approaches used in the generation of nanoparticles. This method of synthesis apart from being a safer method in the production of nanoparticles is also able to control particle morphology. In this study, a comparative biological synthesis, characterization and biomedical effects of metallic nanoparticles of platinum, gold and silver were investigated. Metallic nanoparticles were biologically synthesized using cage-like (apoferritin), barrel-like (GroEL) and non-caged (ribonuclease) proteins. Nanoparticles generated were characterized using common techniques such as UV-visible spectroscopy, scanning and transmission electron microscopy, inductively coupled optical emission spectroscopy, Fourier transform infra-red spectroscopy and energy dispersion analysis of X-rays (EDAX). Nanoparticles synthesised biologically using apoferritin, GroEL and RNase with exhibited similar chemical and physical properties as thoses nanoparticles generated chemically. In addition, the metallic nanoparticles fabricated within the cage-like and barrel-like cavities of apoferritin and GroEL respectively, resulted in nanoparticles with relatively uniform morphology as opposed to those obtained with the non-caged ribonuclease. The enzymatic (ferroxidase) activity of apoferritin was found to be greatly enhanced with platinum (9-fold), gold (7-fold) and silver (54-fold) nanoparticles. The ATPase activity of GroEL was inhibited by silver nanoparticles (64%), was moderately activated by gold nanoparticles (47%) and considerably enhanced by platinum nanoparticles (85%). The hydrolytic activity of RNase was however, lowered by these metallic nanoparticles (90% in Ag nanoparticles) and to a higher degree with platinum (95%) and gold nanoparticles (~100%). The effect of synthesized nanoparticles on the respective enzyme activities of these proteins was also investigated and the potential neurotoxic property of these particles was also determined by an in vitro interaction with acetylcholinesterase. Protein encapsulated nanoparticles with apoferrtin and GroEL showed a decreased inhibition of acetylcholinesterase (<50%) compared with nanoparticles attached to ribonuclease (>50%). Thus, it can be concluded that the cavities of apoferitin and GroEL acted as nanobiofactories for the synthesis and confinement of the size and shape of nanoparticles. Furthermore, the interior of these proteins provided a shielding effect for these nanoparticles and thus reduced/prevented their possible neurotoxic effect and confirmed safety in their method of production and application. The findings from this study would prove beneficial in the application of these nanoparticles as a potential drug/drug delivery vehicle for the prevention, treatment/management of diseases associated with these enzymes/proteins.
Keywords: Nanoparticles; Biosynthesis; Nanotechnology; Biomineralization; Morphology; Ceruloplasmin; Ribonucleases; Adenosine triphosphatase; Acetylcholinesterase; Platinum; Gold; Silver